Lectotype and neotype designations in Dodecastichus Stierlin, 1861 and Otiorhynchus Germar, 1824 (Coleoptera: Curculionidae). - Magnano, Luigi (Contributions to Entomology = Beiträge zur Entomologie, 1998)
Lectotypes of the following species are designated: Dodecastichus heydeni Stierlin, 1861; Otiorhynchus (Acunotus) lutosus Stierlin, 1858; O. (Amosilnus) oberti Faust, (1886); O. (Arammichnus) dobrutschae Stierlin, 1882; O. (Aranihus) misellus Stierlin, 1861; O. (Aranihus) riguus Stierlin, 1883; O. (Choilisanus) affinis Hochhuth, 1847; O. (Choilisanus) caroli Stierlin, 1893; O. (Choilisanus) caucasicus Stierlin, 1872; O. (Choilisanus) schoenherri Stierlin, 1877; O. (Choilisanus) viridisetosus Stierlin, 1905; O. (Egydelenus) jaltensis Formanek, 1926; O. (Elechranus) banaticus Stierlin, 1861; O. (Elechranus) chalceus Stierlin, 1861; O. (Elechranus) roubali Penecke, 1931; O. (Ergiferanus) mus Stierlin, 1862; O. (Lolatismus) chaudoiri Hochhuth, 1851; O. (Lolatismus) depressus Stierlin, 1875; O. (Melasemnus) brevipennis Stierlin, 1892; O. (Melasemnus) crucirostris Hochhuth, 1851; O. (Meriplodus) laconicus Kirsch, 1880; O. (Mitomiris) astutus (Faust, 1886); O. (Mitomiris) laniger Faust, 1887; O. (Namertanus) pseudomias Hochhuth, 1847; O. (Nihus) proximus Stierlin, 1861; O. (Nubidanus) punctirostris Stierlin, 1883; O. (Nubidanus) ruminalis Faust, 1894; O. (Osmobodes) rutilipes Hochhuth, 1851; O. (Osmobodes) tenuimanus Faust, 1890; O. (Osmobodes) venalis Faust, 1888; O. (Otiomimus) desbrochersi Stierlin, 1883; O. (Otiorhynchus) amabilis Stierlin, 1861; O. (Otiorhynchus) auropupillatus Stierlin, 1861; O. (Otiorhynchus) delatus Faust, 1899; O. (Otiorhynchus) latissimus Stierlin, 1861; O. (Otiorhynchus) scaberrimus Stierlin, 1861; O. (Otiorhynchus) steppensis Faust, 1888; O. (Otismotilus) auroguttatus Stierlin, 1879; O. (Paracryphiphorus) nuncius Faust, 1890; O. (Petalorrhynchus) crinitarsis Stierlin, 1861; O. (Phalantorrhynchus) patruelis Stierlin, 1861; O. (Phalantorrhynchus) planidorsis Stierlin, 1886; O. (Pliadonus) schneideri Stierlin, 1876; O. (Tournieria) siewersi Faust, 1888; O. (Podonebistus) alaianus Stierlin, 1886; O. (Podonebistus) bleusei Faust, 1899; O. (Podonebistus) cylindricus Stierlin, 1877; O. (Podonebistus) nefandus Faust, 1888; O. (Podonebistus) prostratus Heyden, 1886; O. (Podonebistus) subparallelus Stierlin, 1893; O. (Prototis) popovi Faust, 1888; O. (Provadilus) carbonarius Hochhuth, 1847; O. (Pseudocryphiphorus) argillosus Hochhuth, 1851; O. (Pseudocryphiphorus) irritabilis (Faust, 1886); O. (Pseudocryphiphorus) zebei Stierlin, 1861; O. (Rimenostolus) auripes Stierlin, 1875; O. (Rusnepranus) arenosus Stierlin, 1861; O. (Rusnepranus) heerii Stierlin, 1858; O. (Stupamacus) erroneus (Faust, 1886); O. (Stupamacus) infensus Faust, 1888; O. (Stupamacus) pilosulus Penecke, 1928; O. (Tournieria) cornicinus Stierlin, 1861; O. (Tournieria) emgei Stierlin, 1887; O. (Tournieria) lubriculus Faust, 1890; O. (Udonedus) koenigi Faust, 1888; O. (Urorrhynchus) truncatus Stierlin, 1861; O. (Zariedus) hystericus Faust, 1892; O. (Zariedus) sedulus Faust, 1894. Neotypes are designated for O. (Amosilnus) pityophilus Gistel, 1857 and of O. (Postaremus) gelidus Gistel, 1857. The following new synonymies (synonyms in square brackets) are established: O. velutinus Germar, 1824 [= O. desbrochersi Stierlin, 1896 (not O. desbrochersi Stierlin, 1883)]; O. laconicus Kirsch, 1880 [= O. oertzeni Stierlin, 1883]; O. nodosus (O. F. Müller, 1754) [= O. gelidus Gistel, 1857]; O. lavandus Germar, 1824 [= O. pityophilus Gistel, 1857]; O. proximus Stierlin, 1861 [= O. depilis Smreczynski, 1959]; O. parvicollis Gyllenhal, 1834 [= O. riguus Stierlin, 1883]; O. caucasicus Stierlin, 1872 [= O. viridisetosus Stierlin, 1905]. Otiorhynchus erroneus (Faust, 1886) is attributed species rank. Otiorhynchus affinis Hochhuth is removed from the synonymy with O. incivilis Faldermann, 1838; O. auroguttatus Stierlin is removed from the synonymy of O. heerii Stierlin, 1858 and transferred from O. (Rusnepranus) Reitter, 1912 to O. (Otismotilus) Reitter, 1912. New combinations are: Otiorhynchus (Rimenostolus) auripes Stierlin from O. (Panorosemus) Reitter, 1913; O. (Rusnepranus) heerii Stierlin from O. (Otismotilus) Reitter, 1912; O. (Stupamacus) infensus Faust from O. (Microphalantus) Reitter, 1912; O. (Elechranus) roubali Penecke from O. (Cryphiphorus) Stierlin, 1883; O. (Pliadonus) siewersi Faust, 1888 from O. (Melasemnus) Reitter, 1912; O. (Podonebistus) alaianus Stierlin, O. (Cryphiphorus) argillosus Hochhuth, O. (Lolatismus) depressus Stierlin, O. (Ergiferanus) mus Stierlin, O. (Podonebistus) prostratus Heyden, O. (Pliadonus) schneideri Stierlin, and O. (Osmobodes) venalis Faust, all thus far listed as species incertae sedis. Nomenclatural Acts heydeni (Stierlin, 1861) (Dodecastichus), Lectotype described as Otiorhynchus heydeni debilis Smreczynski, 1959 (Otiorhynchus), syn. n. of Otiorhynchus (Nihus) proximus Stierlin, 1861 oertzeni Stierlin, 1883 (Otiorhynchus), syn. n. of Otiorhynchus (Meriplodus) laconicus Kirsch, 1880 lutosus Siterlin, 1858 (Otiorhynchus (Acunotus)), Lectotype oberti (Faust, 1886) (Otiorhynchus (Amosilnus)), Lectotype described as Brachyrrhinus oberti pityophilus Gistel, 1857 (Otiorhynchus (Amosilnus)), Neotype; syn. n. of Otiorhynchus lavander Germar, 1824 dobrutschae Stierlin, 1882 (Otiorhynchus (Arammichnus)), Lectotype misellus Stierlin, 1861 (Otiorhynchus (Aranihus)), Lectotype riguus Stierlin, 1883 (Otiorhynchus (Aranihus)), Lectotype; syn. n. of Otiorhynchus parvicollis Gyllenhal, 1834 affinis Hochhuth, 1847 (Otiorhynchus (Choilisanus)), Lectotype; stat. rev. now a valid species caroli Stierlin, 1893 (Otiorhynchus (Choilisanus)), Lectotype caucasicus Stierlin, 1872 (Otiorhynchus (Choilisanus)), Lectotype schoenherri Stierlin, 1877 (Otiorhynchus (Choilisanus)), Lectotype now a synonym of Otiorhynchus caucasicus Stierlin, 1872 viridisetosus Stierlin, 1905 (Otiorhynchus (Choilisanus)), Lectotype; syn. n. of Otiorhynchus caucasicus Stierlin, 1872 jaltensis Formanek, 1926 (Otiorhynchus (Egydelenus)), Lectotype banaticus Stierlin, 1861 (Otiorhynchus (Elechranus)), Lectotype chalceus Stierlin, 1861 (Otiorhynchus (Elechranus)), Lectotype roubali Penecke, 1931 (Otiorhynchus (Elechranus)), Lectotype; comb. n. hitherto Otiorhynchus (Cryphiphorus) roubali mus Stierlin, 1862 (Otiorhynchus (Ergiferanus)), Lectotype; comb. n. hitherto Otiorhynchus mus chaudoiri Hochhuth, 1851 (Otiorhynchus (Lolatismus)), Lectotype depressus Stierlin, 1875 (Otiorhynchus (Lolatismus)), Lectotype; comb. n. hitherto Otiorhynchus depressus brevipennis Stierlin, 1892 (Otiorhynchus (Melasemnus)), Lectotype crucirostris Hochhuth, 1851 (Otiorhynchus (Melasemnus)), Lectotype now a synonym of Otiorhynchus ovalipennis Boheman, 1843 laconicus Kirsch, 1880 (Otiorhynchus (Meriplodus)), Lectotype astutus (Faust, 1886) (Otiorhynchus (Mitomiris)), Lectotype described as Brachyrrhinus (Tournieria) astutus laniger Faust, 1887 (Otiorhynchus (Mitomiris)), Lectotype pseudomias Hochhuth, 1847 (Otiorhynchus (Namertanus)), Lectotype proximus Stierlin, 1861 (Otiorhynchus (Nihus)), Lectotype punctirostris Stierlin, 1883 (Otiorhynchus (Nubidanus)), Lectotype ruminalis Faust, 1894 (Otiorhynchus (Nubidanus)), Lectotype rutilipes Hochhuth, 1851 (Otiorhynchus (Osmobodes)), Lectotype now a synonym of Otiorhynchus cribrosicollis Boheman, 1843 tenuimanus Faust, 1890 (Otiorhynchus (Osmobodes)), Lectotype vernalis Faust, 1888 (Otiorhynchus (Osmobodes)), Lectotype; comb. n. hitherto Otiorhynchus vernalis desbrochersi Stierlin, 1883 (Otiorhynchus (Otiomimus)), Lectotype amabilis Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotype now a synonym of Otiorhynchus amplipennis Fairmaire, 1859 auropupillatus Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotype delatus Faust, 1899 (Otiorhynchus (Otiorhynchus)), Lectotype latissimus Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotype scaberrimus Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotype steppensis Faust, 1888 (Otiorhynchus (Otiorhynchus)), Lectotype now a synonym of Otiorhynchus concinnus Gyllenhal, 1834 auroguttatus Stierlin, 1879 (Otiorhynchus (Otismutilus)), Lectotype; stat. n.; comb. n. now a valid species; hitherto Otiorhynchus (Rusnepranus) auroguttatus nuncius Faust, 1890 (Otiorhynchus (Paracryphiphorus)), Lectotype crinitarsis Stierlin, 1861 (Otiorhynchus (Petalorrhynchus)), Lectotype now a synonym of Otiorhynchus cupreosparsus (Fairmaire, 1859) patruelis Stierlin, 1861 (Otiorhynchus (Phalantorrhynchus)), Lectotype planidorsis Stierlin, 1886 (Otiorhynchus (Phalantorrhynchus)), Lectotype now a synonym of Otiorhynchus moestus Gyllenhal, 1834 schneideri Stierlin, 1876 (Otiorhynchus (Pliadonus)), Lectotype; comb. n. hitherto Otiorhynchus schneideri siewersi Faust, 1888 (Otiorhynchus (Pliadonus)), Lectotype, comb. n. hitrherto Otiorhynchus (Melasemnus) siewersi alaianus Stierlin, 1886 (Otiorhynchus (Podonebistus)), Lectotype; comb. n. hitherto Otiorhynchus alaianus bleusei Faust, 1899 (Otiorhynchus (Podonebistus)), Lectotype cylindricus Stierlin, 1877 (Otiorhynchus (Podonebistus)), Lectotype nefandus Faust, 1888 (Otiorhynchus (Podonebistus)), Lectotype prostratus Heyden, 1886 (Otiorhynchus (Podonebistus)), Lectotype; comb. n. hitherto Otiorhynchus prostratus subparallelus Stierlin, 1893 (Otiorhynchus (Podonebistus)), Lectotype; syn. n. of Otiorhynchus (Podonebistus) cylindricus Stierlin, 1877 gelidus Gistel, 1857 (Otiorhynchus (Postaremus)), Neotype; syn. n. of Otiorhyrhynchus nodosus (O. F. Müller, 1754) popovi Faust, 1888 (Otiorhynchus (Prototis)), Lectotype carbonarius Hochhuth, 1847 (Otiorhynchus (Provadilus)), Lectotype argillosus Hochhuth, 1851 (Otiorhynchus (Pseudocryphiphorus)), Lectotype irritabilis (Faust, 1886) (Otiorhynchus (Pseudocryphiphorus)), Lectotype described as Brachyrrhinus irritabilis zebei Stierlin, 1861 (Otiorhynchus (Pseudocryphiphorus)), Lectotype auripes Stierlin, 1875 (Otiorhynchus (Rimenostolus)), Lectotype; comb. n. hitherto Otiorhynchus (Panorosemus) auripes arenosus Stierlin, 1861 (Otiorhynchus (Rusnepranus)), Lectotype heerii Stierlin, 1858 (Otiorhynchus (Rusnepranus)), Lectotype; comb. n. hitherto Otiorhynchus (Otismotilus) heerii erroneus (Faust, 1886) (Otiorhynchus (Stupamacus)), Lectotype; stat. n. now a valid species infensus Faust, 1888 (Otiorhynchus (Stupamacus)), Lectotype; comb. n. hitherto Otiorhynchus (Microphalantus) infensus pilosulus Penecke, 1928 (Otiorhynchus (Stupamacus)), Lectotype now a synonym of Otiorhynchus clavalis Apfelbeck, 1922 cornicinus Stierlin, 1861 (Otiorhynchus (Tournieria)), Lectotype emgei Stierlin, 1887 (Otiorhynchus (Tournieria)), Lectotype lubriculus Faust, 1890 (Otiorhynchus (Tournieria)), Lectotype koenigi Faust, 1888 (Otiorhynchus (Udonedus)), Lectotype truncatus Stierlin, 1861 (Otiorhynchus (Urorrhynchus)), Lectotype hystericus Faust, 1892 (Otiorhynchus (Zariedus)), Lectotype sedulus Faust, 1894 (Otiorhynchus (Zariedus)), Lectotype